1978
DOI: 10.1079/bjn19780155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin B12deficiency on phosphatidylethanolamine methylation in rat liver

Abstract: I. In vitamin B12 deficiency the activity of tetrahydropteroylglutamate methyltransferase (EC 2 . I . I .13) is depressed and the synthesis of methionine is reduced. Because the methyl group of methionine is largely utilized for the methylation of phosphatidylethanolamine, we investigated the effects of vitamin Bla deficiency on phosphatidylcholine synthesis. Chemical analysis of liver phospholipids showed that the vitamin Bl,-deficient rats had a higher proportion of phosphatidylethanolamine and a lower propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
4
5
1
Order By: Relevance
“…Previous studies on the response of methyltransferase to cobalamin deficiency have shown a reduction in hepatic enzyme activity in rats [21], fruit bats [25] and chickens [26]. In contrast, the present studies did not show a decrease in either holoenzyme or total enzyme activity, but instead an increase in hepatic holoenzyme activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on the response of methyltransferase to cobalamin deficiency have shown a reduction in hepatic enzyme activity in rats [21], fruit bats [25] and chickens [26]. In contrast, the present studies did not show a decrease in either holoenzyme or total enzyme activity, but instead an increase in hepatic holoenzyme activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study also confirms a previous report (Akesson et al 1978), where vitamin B,,-deficient rats were shown to have reduced ability to methylate phospholipids in their livers. This is consistent with a depressed activity of the vitamin BIZ-dependent methyltransferase reaction producing less methionine for methyl group transfer (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…No change of vitamin B 12 plasma level was observed in MD diet-fed rats. This emphasizes that a vitamin B 12 -free diet cannot be considered efficient enough to provide a severe and permanent vitamin B 12 deficiency in rats [19, 23]. It is therefore likely that coprophagy provides enough vitamin B 12 , even when the vitamin B 12 diet is restricted.…”
Section: Discussionmentioning
confidence: 99%